Improving the Bearing Capacity of soil Using Alkali activated fly ash-based geopolymer (University of Thi-Qar Journal for Engineering Sciences, 2023)
Geopolymer has introduced recently as a novel echo-friendly alternative to the tradition materials of soil stabilization such as lime and Ordinary Portland Cement (OPC) to eliminate their sever impacts on the environment. Geopolymers involve alkaline activation of industrial waste to create cementitious products in treated soils, resulting with in improved soil properties. Due to its low bearing capacity, weak soil presents a problematic ground condition that is almost unsuitable for engineering construction projects. Chemical stabilization is one of the most widely used methods to enhance weak soil properties such bearing capacity. Therefore, this paper investigated the strength of low plasticity silt treated by geopolymer. The results shows that the unconfined compressive strength (UCS) of the low plasticity silt-geopolymer matrix increased significantly in range of with increasing the main ingredient of the geopolymer (FGP), i.e., fly ash (FA). Similar trend was observe regarding to the secant modulus. However, with increasing the activator ratio, the compressive strength of soil-geopolymer matrix decreased for fly ash content of 20-30% and increased when the fly ash was 5-15%. The improvement in the strength is attributed to the dense and stiff crystalline structure due to fill the low plasticity silt voids by fly ash, produce geopolymer hydrated gel (C, N–A–S–H) that significantly bonded the soil particles. Therefore, it can be concluded that geopolymer is viable sustainable material to improve such problematic soil for different applications.